WHY MASS APPEARS GRAVITATIONAL - Ray McMahon, Mr Casey (JOURNAL OF ADVANCES IN PHYSICS, 2016)
Einsteins theory of General relativity is a popular theory, but unfortunately it cannot account for all the observable gravity in the universe. This paper presents a new force predicted through the McMahon field theory (2010) [1], which is refered to in McMahon field theory (2010) [1] as Mahona (pronounced Maa-naa), which appears to be gravitational. In this paper, I draw upon the McMahon field theory (2010) [1], and use it to explain why mass appears gravitational, as well as the source of the excess gravity that General relativity cannot account for. I will do this in simplistic terms for the benefit of the reader. Thus with the understanding presented here, any vechicle utilising this new force called Mahona shall have gravitational capability.